Promotion of breastfeeding: an integrative review of educational practices (Research, Society and Development, 2021)
Objective: to understand the educational practices involved with pregnant and postpartum women regarding breastfeeding. Method: This is an integrative review, of exploratory nature, which aims to gather and synthesize information and research results in order to answer the guiding question: what are the educational practices used by health professionals to guide women regarding breastfeeding. Results: regarding the professionals involved in breastfeeding education, the articles indicated mainly the multidisciplinary team, including the doctor, the nurse, the nursing technician, and the community health workers; regarding the analysis of the places and times when women are guided, the articles pointed out the prenatal consultations in the Basic Health Units (BHU) as the time and place chosen for the guidance; and regarding the educational practices used, a variety of practices is verified, where the groups for pregnant women show themselves to be the most relevant strategy. Conclusion: it was possible to observe that the strategies and actions carried out by the multidisciplinary team from the follow-up during prenatal care to the moment of maternity and postpartum are extremely important for the success of breastfeeding. It is also essential to carry out various educational activities, especially the formation of groups of pregnant women, in person or online, that promote EBF, strengthening the mother/baby care network and minimizing early weaning.